Thin piezoelectric layers of Pb(Zr,Ti)O3 obtained by the sol-gel method - SZALEWSKI, M.; WOLNA, M. (Archives of Acoustics, 1997)
In the paper the method of obtaining of thin layers of Pb(Zr,Ti)O3 ceramics and the results of their preliminary investigations are presented. The layers have been obtained by the sol-gel technology. They were deposited on anodized surfaces of plates, parallelepipeds and cylinders of Al. The existence of ferroelectric (hysteresis loop) and piezoelectric (in poled layers) properties has been ascertained. The possibility of the application of those layers as ultrasonic transducers in the range of high frequencies has been proved using them for generation and reception of pulses of ultrasonic longitudinal waves.